An optimized sporulation method for the wheat fungal pathogen Pyrenophora tritici-repentis - Jacques, Silke; Lenzo, Leon; Stevens, Kofi; Lawrence, Julie; Tan, Kar-Chun (BioMed Central, 2021)
Background: